ORNAMEN KACA PADA INTERIOR BANGUNAN TRADISIONAL DI SURAKARTA - Agung Purnomo (Institut Seni Indonesia Surakarta, 2009)
Glass is kind of material often used in building planning including in the interior part. Glass, with several characteristics and special qualities, is able to give beauty and comfortable atmosphere in a room. This recearch aims at the application the material of glass in the common building interior which characterize Javanese traditional house, viewed from the meaning of ornamentation and its function. Recearch locates in Surakarta possessed of many common building with architecture characterizing Javanese tradisional house. The research is descriptive qualitative analytic bu applying design approach in this matter related to the function and fine arts language (semiotic fine arts language) to analyze its ornamentation side. The sources of data are books and artifact. Technicque of collecting data is conducted by book study, observation, and dokumentation. Analyzing technique uses interactive analytic miodel and drawing conclusion or its verification, the activity is conducted interactively by using data collection process as taken purposively by using creteria wich is glass element applied having ornamentation form, meaning and fungtion. Sample chosen are Pendapi Gede Balaikota (City Hall) which is part of complex of local government office of Surakarta and Sasana Handrawina Kasunanan Palace of Surakarta as a tourism attraction wich is able to be visited and utilized by public. The ornament applied in Pendapi Gede Balaikota (City Hall) of Surakarta is a symbol of the local government of Surakarta, while the ornament used in Sasana Handrawina is a symbol called Radya Laksana. Inside the symbol used as ornaments of both buildings, there are various raut or shape having meaning related to cosmos, food dan clothing, hassle, and culture. For example is the shape of of the sun having meaning that a person having cultural spirit must be able to engraft power and must be able to shine a light of life without expecting for the return. The function of ornaments in the shape of the symbols is not addressed for sacred importance but to fullfill the profane needs wich ae beauty or aesthetic value and used an identity. Key words : interior, glass, ornament